Root ABA and H+‐ATPase are key players in the root and shoot growth‐promoting action of humic acids. (10th October 2019) - Olaetxea, Maite; Mora, Verónica; Bacaicoa, Eva; Baigorri, Roberto; Garnica, Maria; Fuentes, Marta; Zamarreño, Angel Maria; Spíchal, Lukáš; García‐Mina, José María
Abstract: Although the ability of humic (HA) and fulvic acids (FA) to improve plant growth has been demonstrated, knowledge about the mechanisms responsible for the direct effects of HA and FA on the promotion of plant growth is scarce and fragmentary. Our study investigated the causal role of both root PM H + ‐ATPase activity and ABA in the SHA‐promoting action on both root and shoot growth. The involvement of these processes in the regulation of shoot cytokinin concentration and activity was also studied. Our aim was to integrate such plant responses for providing new insights  to the current model on the mode of action of HA for promoting root and shoot growth. Experiments employing specific inhibitors and using Cucumis sativus L. plants show that both the root PM H + ‐ATPase activity and root ABA play a crucial role in the root growth‐promoting action of SHA. With regard to the HA‐promoting effects on shoot growth, two pathways of events triggered by the interaction of SHA with plant roots are essential for the increase in root PM H + ‐ATPase activity—which also mediates an increase in cytokinin concentration and action in the shoot—and the ABA‐mediated increase in hydraulic conductivity (Lpr ).